(DES)fazendo Saberes, lutas e (re)existências: as diversidades em foco - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present work aims to present the path taken by the GEEP - Research Group in Gender, Ethics, Education and Politics at the Federal University of Pampa, São Borja campus and the challenges for expansion of debates on gender, sexuality, diversity, ethnic and racial relations in a region of frontier, historically called machismo, sexism and patriarchy. For that, we weave some reflections on the projects developed and the results achieved. Added to this is the perspective of ethnography and autoethnography of the project participants, especially the coordinator and founder of the Dra. Jaqueline Carvalho Quadrado project. Finally, we consider that the actions developed are fundamental for the expansion of discussions on social markers of difference in the municipality of São Borja and the training of several professionals and students in the basic education network.
(DES)making Knowledge, struggles and (re)existences: the diversities in focus
Keywords: Direitos humanos; Pandemia; Racismo; Homofobia; Relações de genero; Violência sexual; Human rights; Pandemic; Racism; Homophobia; Gender relations; Sexual violence; CNPQ::CIENCIAS HUMANAS